Overview of meta‐analysis on prevention and treatment of childhood obesity - Luciana Bahia; Camila Wohlgemuth Schaan; Karen Sparrenberger; Gabriela de Azevedo Abreu; Laura Augusta Barufaldi; Walmir Coutinho; Beatriz D. Schaan (Brazilian Society of Pediatrics, 2019)
Objectives: This study aimed to assess the quality of systematic reviews on prevention and non‐pharmacological treatment of overweight and obesity in children and adolescents. Data source: A search was done in electronic databases (Medline via PubMed, Web of Science, Scopus, LILACS, the Cochrane Library, and Clinical Trials), including only systematic reviews with meta‐analysis. Reviews were selected by two researchers, and a third one solved the divergences. PRISMA statement and checklist were followed. Summary of data: A total of 4574 records were retrieved, including 24 after selection. Six reviews were on obesity prevention, 17 on obesity treatment, and one on mixed interventions for prevention and treatment of obesity. The interventions were very heterogeneous and showed little or no effects on weight or body mass index. Mixed interventions that included dieting, exercise, actions to reduce sedentary behavior, and programs involving the school or families showed some short‐term positive effects. Reviews that analyzed cardiovascular risk factors demonstrated significant improvements in the short‐term. Conclusion: The systematic reviews of interventions to prevent or reduce obesity in children and adolescents generally showed little or no effects on weight or body mass index, although cardiovascular profile can be improved. Mixed interventions demonstrated better effects, but the long‐term impact of obesity treatments of children and adolescents remains unclear. Resumo: Objetivos: Este estudo teve como objetivo avaliar a qualidade das revisões sistemáticas sobre prevenção e tratamento não farmacológico do sobrepeso e da obesidade em crianças e adolescentes. Fontes de dados: Foi realizada uma busca em bases de dados eletrônicas (Medline via Pubmed, Web of Science, Scopus, LILACS, The Cochrane Library e Ensaios Clínicos), incluindo apenas revisões sistemáticas com meta-análise. As revisões foram selecionadas por dois pesquisadores e um terceiro resolveu as divergências. A lista de recomendações do PRISMA foi seguida. Síntese dos dados: Foram identificados 4.574 publicações, e 24 foram incluídas após seleção. Seis publicações eram sobre prevenção da obesidade, 17 sobre tratamento da obesidade e 1 sobre intervenções mistas para prevenção e tratamento da obesidade. As intervenções eram muito heterogêneas e mostraram pouco ou nenhum efeito sobre o peso ou índice de massa corporal. Intervenções mistas que incluíam dieta, exercícios, ações para reduzir o comportamento sedentário e programas que envolviam a escola ou as famílias mostraram alguns efeitos positivos de curto prazo. Revisões que analisaram fatores de risco cardiovascular demonstraram melhoras significativas em curto prazo. Conclusão: As revisões sistemáticas de intervenções para prevenir ou reduzir a obesidade em crianças e adolescentes geralmente mostraram pouco ou nenhum efeito sobre o peso ou índice de massa corporal, embora o perfil cardiovascular possa ter melhorado. Intervenções mistas demonstraram melhores efeitos, mas o impacto em longo prazo dos tratamentos da obesidade de crianças e adolescentes ainda não está claro. Keywords: Child, Adolescent, Obesity, Palavras‐chave: Criança, Adolescente, Obesidade